Dampak Daya Tarik Wisata Danau Weekuri Terhadap Ekonomi dan Sosial Masyarakat Desa Moro Manduyo Sumba Barat Daya - Maria Efliana Pratama Mori Ate; Maria Makdalena Bokol; Dominggus Kaleka; Hesron Musa Dappa; Hugolin Arvin Lende Wara (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study aims to analyze the tourist attraction of Lake Weekuri on the economy and social community of Moro Mandoyo Village. Lake Weekuri, located in Southwest Sumba Regency, East Nusa Tenggara, has become an increasingly popular tourist destination in recent years. The natural beauty and cultural richness of Lake Weekuri attracts both domestic and foreign tourists. This study uses a qualitative approach with interview, observation, and documentation study methods to collect data related to the impact of tourist visits on the local economy and social changes in the local community. The results of the analysis show that the existence of Lake Weekuri has a positive impact on the community's economy, especially in the tourism, trade, and small and medium enterprises (SMEs) sectors. The increase in the number of tourists has created new job opportunities, increased community income, and encouraged the development of local infrastructure. However, there are also challenges related to the management of tourist destinations that need to be considered to ensure the sustainability of these positive impacts. Socially, the development of the tourism sector has brought changes in people's lifestyles, both in cultural, social, and educational aspects. The people of Moro Mandoyo Village are increasingly open to changes and opportunities offered by tourism, but also face challenges in maintaining the sustainability of local culture and the balance between tradition and modernity. This study provides recommendations for more sustainable tourism management, which takes into account community needs and environmental conservation, so as to maximize economic and social benefits for the people of Moro Mandoyo Village.